Cardiac tamponade caused by acute coxsackievirus infection related pericarditis complicated by aortic stenosis in a hemodialysis patient: a case report - Azumi Hamasaki; Tetsuro Uchida; Atsushi Yamashita; Kentaro Akabane; Mitsuaki Sadahiro (Surgical Case Reports, 2018)
Abstract Background Pericardial effusion is observed in the majority of viral pericarditis cases; however, viral pericarditis accompanied by a large effusion resulting in cardiac tamponade is rare. Case presentation Here, we report the case of a 75-year-old hemodialysis patient with acute viral pericarditis complicated by aortic stenosis. The patient was referred with a diagnosis of aortic stenosis and pericardial effusion. The pericardial effusion had increased during the preoperative examinations, and the inflammatory reaction had progressed. We decided to abort the surgical intervention and start oral administration of anti-inflammatory agents. We subsequently performed a pericardiocentesis. High antibody titers to coxsackievirus were noted in the pericardial effusion. Since no recurrence of the pericardial effusion was observed, the patient underwent an aortic valve replacement 2 months later. The pericardium completely adhered to the heart. Pathological examination of the pericardium showed fibrous pericarditis without active inflammation. Conclusions Here, we successfully treated a hemodialysis case with severe aortic stenosis complicated by cardiac tamponade and worsened by acute viral pericarditis. We waited for the pericarditis to resolve after administering anti-inflammatory agents and performed pericardial drainage before carrying out aortic valve replacement. The perioperative course of our case was unique and suggestive.